The Covid-19 pandemic and the mental illness of pregnant womem (Research, Society and Development, 2021)
This study aims to discuss, based on scientific literature, the mental illness of pregnant women during the current Covid-19 pandemic. This is an integrative review study, with a search carried out in the Nursing Database, Latin American and Caribbean Literature on Health Sciences, Bibliographic Index Español en Sciences de la Salud, Medical Literature on Line and Cumulative Index to Nursing and Allied Health Literature, during the months of October and November 2020. The following descriptors were used: ''Pregnant women'', 'Mental disorders' and ''Coronavirus''. After screening the productions, five were included as a study sample. Of the publications included, all had a quantitative approach. Three publications were classified as Level of Evidence III (well-designed clinical trial without randomization). The main results were the presence of symptoms of anxiety, depression and stress and their negative impacts that contribute to the psychological distress of pregnant women during the pandemic period. During the Covid-19 pandemic, pregnant women are more vulnerable and may suffer from mental illness, with emphasis on the appearance of symptoms related to mental disorders.